Cell sheet produced from periodontal ligament stem cells activated by PAR1 improves osteogenic differentiation - Letícia Miquelitto GASPARONI; Tomaz ALVES; Bruno Nunes de FRANÇA; Danilo BALZARINI; Emmanuel ALBUQUERQUE-SOUZA; Ana Clara Fagundes PEDRONI; Emanuel da Silva ROVAI; Aldrin Huamán MENDOZA; Carla Renata SIPERT; Marinella HOLZHAUSEN (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Periodontal regeneration is a challenge, and tissue engineering based on periodontal ligament stem cells (PDLSCs) has been shown to be a promising alternative to this process. However, the need for scaffolds has limited the therapeutic use of PDLSCs. In this context, scaffold-free tissue engineering using the cell sheet (CS) technique has been developed as an alternative approach to improve tissue regeneration. Previously, we showed that Protease-activated receptor-1 (PAR1) can regulate PDLSCs. Herein, we evaluate whether PAR1 influences osteogenesis in CSs produced from PDLSCs, without the use of scaffolds. PDLSCs were isolated and immunophenotyped. Then, CSs were obtained by supplementing the culture medium with ascorbic acid (50 µg/mL), and PAR1 was activated through its agonist peptide (100 nM). Scaffold-free 3D CSs were successfully produced from PDLSCs, and they showed higher proliferation potential than isolated PDLSCs. Also, PAR1 activation decreased senescence and improved osteogenic differentiation of CSs by increasing mineralized nodule deposition and alkaline phosphatase concentration; PAR1 also modulated osteogenic markers at the gene and protein levels. We further demonstrated that this effect was regulated by Wnt, TGF-βI, MEK, p38 MAPK, and FGF/VEGF signaling pathways in PDLSCs (p < 0.05%). Overall, PAR1 activation increased osteogenic activity in CSs, emerging as a promising scaffold-free therapeutic approach for periodontal regeneration.